The association of late-life depression with all-cause and cardiovascular mortality among community-dwelling older adults: systematic review and meta-analysis. (August 2019) - Wei, Jingkai; Hou, Ruixue; Zhang, Xiaotao; Xu, Huiwen; Xie, Liyang; Chandrasekar, Eeshwar K.; Ying, Meiling; Goodman, Michael
Abstract : Background: Late-life depression has become an important public health problem. Available evidence suggests that late-life depression is associated with all-cause and cardiovascular mortality among older adults living in the community, although the associations have not been comprehensively reviewed and quantified. Aim: To estimate the pooled association of late-life depression with all-cause and cardiovascular mortality among community-dwelling older adults. Method: We conducted a systematic review and meta-analysis of prospective cohort studies that examine the associations of late-life depression with all-cause and cardiovascular mortality in community settings. Results: A total of 61 prospective cohort studies from 53 cohorts with 198 589 participants were included in the systematic review and meta-analysis. A total of 49 cohorts reported all-cause mortality and 15 cohorts reported cardiovascular mortality. Late-life depression was associated with increased risk of all-cause (risk ratio 1.34; 95% CI 1.27, 1.42) and cardiovascular mortality (risk ratio 1.31; 95% CI 1.20, 1.43). There was heterogeneity in results across studies and the magnitude of associations differed by age, gender, study location, follow-up duration and methods used to assess depression. The associations existed in different subgroups by age, gender, regions of studies, follow-up periods and assessment methods of late-life depression. Conclusion: Late-life depression is associated with higher risk of both all-cause and cardiovascular mortality among community-dwelling elderly people. Future studies need to test the effectiveness of preventing depression among older adults as a way of reducing mortality in this population. Optimal treatment of late-life depression and its impact on mortality require further investigation. Declaration of interest: None.